Quaternary depositional patterns and sea-level fluctuations, northeastern North Carolina - Parham, P. R.; Riggs, S. R.; Culver, S. J.; Mallinson, D. J.; Wehmiller, J. F. (Quaternary Research, 2007)
A detailed record of late Quaternary sea-level oscillations is preserved within the upper 45 in of deposits along an eight kin transect across Croatan Sound, a drowned tributary of the Roanoke/Albemarle drainage system, northeastern North Carolina. Drill-hole and seismic data reveal nine relatively complete sequences filling an antecedent valley comprised of discontinuous middle and early Pleistocene deposits. On interfluves, lithologically similar marine deposits of different sequences occur stacked in vertical succession and separated by ravinement surfaces. Within the paleo-drainage, marine deposits are separated by fluvial and/or estuarine sediments deposited during periods of lowered sea level. Foraminiferal and molluscan fossil assemblages indicate that marine facies were deposited in a shallow-marine embayment with open connection to shelf waters. Each sequence modifies or truncates portions of the preceding sequence or sequences. Sequence boundaries are the product of a combination of fluvial, estuarine, and marine erosional processes. Stratigraphic and age analyses constrain the ages of sequences to late Marine Isotope Stage (MIS) 6 and younger (similar to 140 ka to present), indicating multiple sea-level oscillations during this interval. Elevations of highstand deposits associated with late MIS 5 and MIS 3 imply that sea level was either similar to present during those times, or that the region may have been influenced by glacio-isostatic uplift and Subsidence. (c) 2006 University of Washington. All rights reserved.
131tvTimes Cited:18Cited References Count:56